Assessment of the Antimalarial Treatment Failure in Ebonyi State, Southeast Nigeria - Chinedu Ogbonnia Egwu; Chinyere Aloke; Jennifer Chukwu; Joshua Chidiebere Nwankwo; Chinemerem Irem; Kingsley E. Nwagu; Felix Nwite; Anthony Ogbonnaya Agwu; Esther Alum; Christian E. Offor; Nwogo Ajuka Obasi (MDPI AG, 2023)
The fight against malaria is a continuum as the epidemic is not abating. For proper deployment of tools in the fight against malaria, an assessment of the situation is necessary. This work assessed the level of antimalarial drug treatment failure in Ebonyi State, Nigeria. Both survey and in vitro analyses were adopted. The survey was used to obtain qualitative information from both the malaria subjects and the pharmacies where antimalarial drugs are sourced. The results from the survey were complemented by an in vitro assay of the level of active pharmaceutical ingredients (APIs) in the commonly used artemisinin combination in Nigeria; artemether/lumefantrine. Results from the survey revealed that artemisinin combination therapies (ACTs) remain the mainstay in the treatment of malaria, even though other non-artemisinin drugs are still used. It also revealed that many patients still self-medicate, although, this may not be connected to the treatment failure seen among some malaria subjects. The in vitro assay showed that ACT contains the right quantity of APIs. Further surveillance is, therefore, necessary to understand the real cause of treatment failure among malaria subjects in Nigeria.